Influence of antibiotics on formylmethionyl-leucyl-phenylalanine-induced leukocyte chemiluminescence. - Briheim, G (1987)
The effect of three antimicrobial agents, penicillin G, ampicillin, and chloramphenicol, on luminol-enhanced chemiluminescence of polymorphonuclear leukocytes stimulated by the chemoattractant formylmethionyl-leucyl-phenylalanine was studied. An inhibitory effect of penicillin G and of ampicillin was demonstrated, whereas chloramphenicol gave rise to an enhancement of the chemiluminescence response from polymorphonuclear leukocytes. These effects could be due to interaction between the drugs and the polymorphonuclear leukocytes, but they could also be the result of interference with the generation of light without any effect on the cells. Therefore, the effects of the same antimicrobial agents on the chemiluminescence generated from a cell-free system consisting of myeloperoxidase and hydrogen peroxide were investigated in parallel. The results obtained in the cell-free system were almost identical to those obtained in the cell system; i.e., penicillin G and ampicillin caused an inhibition and chloramphenicol caused an enhancement of the light emission. These results indicate that observed effects induced by drugs in a chemiluminescence assay are not necessarily due to interaction between the drug and polymorphonuclear leukocytes but may be caused by interference with other components of the assay. In view of these findings, the conflicting data reported in the literature on the effects of antimicrobial agents on phagocyte function are discussed.